Progressive Development of Appendicular and Axial Skeletons in Guinea Fowl (Numida meleagridis) Embryo - Onyeanusi, B.I.; Sulaiman, M.H.; Salami, S.O.; Maidawa, S.M.; Umosen, A.D.; Byanet, O.; Nzalak, J.O.; Ali, M.N.; Imam, J. (International Journal of Poultry Science, 2008)
From day one to day nine of embryonic development, no ossification centre was observed in the embryo. Small centres of ossification were seen on the 10th day at some locations like the cervical vertebrae, thoracic vertebrae, clavicle, coracoid, scapula, humerus, radius and ulna. Other areas with centres of ossification on this day included the ilium, pubis, femur and fibular. By day 12, these centres of ossification were very prominent at the points seen on day 10 and in addition, the Ischium had ossification centre. By day 13, ossification centres showed up in lumbosacral vertebrae, radius ulna, ulnacarpal and carpometacarpal joints, metatarsus, tibiotarsus, patella, first phalanx of digit ii and second phalanx of digit iii. Between days 15 and 16, additional ossification centres were observed at coccygeal vertebrae, digits ii, iii and iv of pectoral limb. By day 21, ossification centre appeared on the pygostyle and by days 23 and 24, the right and left clavicles had joined together although not properly fused.